071 SAFETY AND EFFICACY OF PARAMEDIC TREATMENT OF REGULAR SUPRAVEENTRICULAR TACHYCARDIA. (24th May 2013) - Baker, A; Whitbread, M; Richmond, L; Kirkby, C; Robinson, G; Antoniou, S; Schilling, R
Abstract : Introduction: Treatment of supraventricular tachycardia (SVT) with adenosine by paramedics has been investigated and proven to be safe in the USA, but patients (pts) are transferred to hospital. We hypothesised that paramedics can safely treat and discharge pts with regular SVT without transfer to an accident and emergency department and tested this in a randomised controlled trial. Methods: Pts presenting with regular narrow complex tachycardia on 12 lead ECG who were heamodynamically stable, with no history of structural or ischaemic heart disease and without contraindication to adenosine were considered for enrolment. Pts were randomised to paramedic treatment (PARA) or admission to hospital (A&E). PARA pts received valsalva manoeuvre at the scene with subsequent administration of 6 mg and 12 mg of adenosine unless the SVT terminated. Pts were taken to A&E if the tachycardia did not terminate, restarted, or the patient (pt) had continuing symptoms, a persistently abnormal ECG (other than T wave inversion) or was heamodynamically unstable. Prior to discharge from the ambulance pts received an information pack and a referral letter for their GP to refer them to an arrhythmia clinic. Pts randomised to A&E were treated as normal and given no information other than that pertaining to the study. Results: Of the 60 pts (33=F, age 52±19 years) enroled to date, 56% pts had previously attended A&E with palpitations. 2 pts withdrawn as lost to follow up. Results table 1 PARA discharge times were relatively long because 12 pts randomised to PARA were transported to A&E (5 did not terminate arrhythmia, 1 abnormal observations, 4 paramedic felt ECG abnormal (confirmed as minor abnormalitites by expert panel that would not require treatment), 2 abnormal ECG requiring treatment). A panel of 2 arrhythmia experts reviewed records for all PARA pts and confirmed treatment was appropriate for all but would have further assessed 1 pt with lung disease. Conclusions: Paramedic treatment and discharge of pts with regular SVT is safe, efficacious and reduces admissions. Cost effectiveness analysis is ongoing.